Preparation method for improving charge-discharge efficiency and cycle performance of silicon-oxygen negative electrode material

Through the combination of modified SiOx material and conductive polymer and the introduction of silicon-containing adhesives, the structural problems caused by expansion of the negative electrode material of lithium battery are solved, the charging and discharging efficiency and cycling performance are improved, and more stable battery performance is achieved.

CN119315023APending Publication Date: 2025-01-14YANGZHOU NANOPORE INNOVATIVE MATERIALS TECH LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411556920.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

The existing lithium battery negative electrode materials such as graphite cause core deformation, cavity between electrodes and separators, and microcracks of negative electrode particles due to large expansion coefficients. The existing silicon oxygen material preparation methods are costly and unstable in performance, making consistency difficult to ensure.

Method used

Using a method for improving the preparation of silicon oxygen negative electrode materials, the modified SiOx material is obtained by stirring the SiOx material with polymethyl methacrylate emulsion and conductive polymer material evenly, conducting hydrothermal reaction, filtering and drying, and obtaining the modified SiOx material and sticking to the A silicon-containing binder is introduced into the assembly agent to form a negative electrode slurry, coated on the current collector and dried to prepare a high-performance silicon oxygen negative electrode material.

Benefits of technology

The charge and discharge efficiency and cycling performance of silicon oxygen negative electrode materials are improved, the structural changes of the battery during the charge and discharge process are reduced, the service life of the battery is extended, and the overall performance of the battery is improved through excellent adhesion and conductivity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the field of lithium batteries, in particular to a preparation method for improving charge-discharge efficiency and cycle performance of a silicon-oxygen negative electrode material. Comprising the following steps: 1, adding a SiOx material into pure water, adding a polymethyl methacrylate emulsion and a conductive polymer material, uniformly stirring, transferring into a reaction kettle, carrying out thermal reaction, filtering, and drying to obtain a modified SiOx material; 2, preparing a silicon-oxygen negative electrode material from the modified SiOx material; the silicon-oxygen negative electrode material is obtained; and the charge-discharge efficiency, the cycle performance and other electrical properties are effectively improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium batteries, and in particular to a preparation method for improving the charge-discharge efficiency and cycle performance of silicon-oxygen negative electrode materials. Background Art

[0002] With the rapid development of the new energy industry, people's pursuit of battery life has gradually increased. Among them, lithium batteries have developed rapidly in the new energy field due to their excellent high energy density characteristics.

[0003] The negative electrode material of lithium batteries is mostly graphite. Although graphite has a high theoretical charge and discharge capacity, it has problems such as a large expansion coefficient, which can cause deformation of the winding core, formation of voids between the electrode and the diaphragm, and microcracks in the negative electrode particles. To solve this series of problems, silicon-oxygen materials came into being. In the existing technology, high-quality silicon-oxygen films or coatings can be prepared by carbon thermal reduction and chemical vapor deposition, but the equipment cost is high and the reaction conditions need to be precisely controlled. The performance of the prepared silicon-oxygen materials may fluctuate greatly, and it is difficult to ensure consistency.

[0004] In summary, it is of great significance to solve the above problems and prepare a silicon-oxygen negative electrode material. Summary of the invention

[0005] The purpose of the present invention is to provide a preparation method for improving the charge-discharge efficiency and cycle performance of silicon-oxygen negative electrode materials, so as to solve the problems raised in the above-mentioned background technology.

[0006] In order to solve the above technical problems, the present invention provides the following technical solutions: A preparation method for improving the charge-discharge efficiency and cycle performance of silicon-oxygen negative electrode materials comprises the following steps: Step 1: Add SiOx material to pure water, add polymethyl methacrylate emulsion and conductive polymer material and stir evenly, transfer to a reactor for reaction, filter and dry to obtain modified SiOx material; Step 2: Use the modified SiOx material to prepare silicon-oxygen negative electrode material.

[0007] More optimally, the solid content of the polymethyl methacrylate emulsion is 14.5-15.5%; the mass ratio of the SiOx material to the solid in the polymethyl methacrylate emulsion is 115-135:1.

[0008] More optimally, the mass ratio of the SiOx material to the conductive polymer material is 95-115:1.

[0009] More optimally, in step 1, the reaction conditions are: baking at 180-200° C. for 12-16 hours; The specific steps of step 2 are: uniformly mixing the modified SiOx material, the binder, and the conductive agent to obtain a negative electrode slurry; coating the negative electrode slurry on the current collector, and drying at 100-120° C. for 12-16 hours to obtain a silicon-oxygen negative electrode material.

[0010] More optimally, the raw materials of the negative electrode slurry include modified SiOx material, a binder, and a conductive agent in a mass ratio of 8:1:1.

[0011] Preferably, the current collector comprises copper foil; and the thickness of the current collector is 6-10 μm.

[0012] More optimally, the adhesive includes one or both of an LA-type water-based adhesive and a silicon-containing adhesive.

[0013] More optimally, the binder is composed of an LA-type water-based binder and a silicon-containing binder, and the silicon-containing binder accounts for 20-30wt% of the total binder.

[0014] More optimally, the preparation method of the silicon-containing binder is: Step 1: (1) under nitrogen atmosphere, add bisaminosilane oligomer, triethylenetetramine, 2-(methylacrylate)ethyl-3,5-diaminobenzoic acid, and thiocarbonyldiimidazole to N-methylpyrrolidone, react at 25-35° C. for 18-24 hours, add phenylpropanol for end-capping, and post-treat to obtain a silicon-containing intermediate; Step 2: Add the silicon-containing intermediate, mercaptoaniline, mercaptosiloxane, and azobisisobutyronitrile (AIBN) to N,N-dimethylformamide (DMF), irradiate with ultraviolet light for 2 to 3 hours at room temperature, wash, and dry to obtain a silicon-containing adhesive.

[0015] In a further scheme, the specific process of the post-treatment is: after end-capping, acetone is added for dilution, followed by precipitation with ethyl acetate, washing and centrifugation at 7000-8500 r / min for 10-15 min, repeated 2-3 times, dried, and then dried at 80-90°C for 12-15 hours to obtain a silicon-containing intermediate.

[0016] More optimally, the raw materials of the silicon-containing intermediate include the following components: by mass, 5-6 parts of bisaminosilane oligomer, 2-3 parts of triethylenetetramine, 4-5 parts of thiocarbonyldiimidazole, 4-5 parts of 2-(methacrylate)ethyl-3,5-diaminobenzoic acid, 2-3 parts of phenylpropanol, and 80-100 parts of N-methylpyrrolidone; The raw materials of the silicon-containing adhesive include the following components: by mass, 14 to 16 parts of silicon-containing intermediate, 2 to 3 parts of mercaptoaniline, 1 to 2 parts of mercaptosiloxane, 0.1 to 0.12 parts of azobisisobutyronitrile (AIBN), and 80 to 100 parts of N,N-dimethylformamide (DMF).

[0017] In the scheme, a silicon-containing binder is introduced into the binder to effectively enhance the dispersibility of the negative electrode slurry while improving the adhesion, thereby improving the electrical properties of the negative electrode material.

[0018] Among them, the silicon-containing adhesive is based on a diamino silane oligomer, and forms a dynamic hydrogen bond adhesive through hydrogen bonding with triethylenetetramine, 2-(methacrylate)ethyl-3,5-diaminobenzoic acid, and thiocarbonyldiimidazole; and utilizes the unsaturated group of 2-(methacrylate)ethyl-3,5-diaminobenzoic acid, and subsequently grafts mercaptoaniline and mercaptosiloxane through thiol click chemistry to obtain a silicon-containing adhesive.

[0019] Among them, the silicon-containing binder, through the network structure formed by amino reaction and imidazole ring cross-linking, can effectively increase the adhesion between the active material (such as SiOx) and the current collector, reduce the impact of thermal stress, and reduce the shedding and pulverization of the active material during charging and discharging, thereby improving the charging and discharging efficiency of the battery.

[0020] The silane chain segments contained in it have good affinity with SiOx materials. At the same time, the silicon chain is heat-resistant and tough, which helps to maintain the structural integrity of the negative electrode material, so that it can better withstand the stress caused by volume expansion and contraction during the cycle, reduce structural changes in the charge and discharge cycle, further improve the charge and discharge efficiency, and extend the service life of the battery.

[0021] The special structures (such as imidazole ring, etc.) contained in it also have a certain electron transmission ability, which further promotes the electron conduction of the negative electrode material. The aniline structure contained in it can improve the similar compatibility with the modified SiOx material; and the siloxane contained in it can promote the dispersion of the conductive agent, thereby improving the dispersibility of the slurry, improving the formation of a uniform cross-linked network, improving ion mobility, and increasing electrical properties.

[0022] Compared with the prior art, the present invention has the following beneficial effects: 1. The conventional one-step hydrothermal method is used in the scheme to prepare the modified SiOx material. The conventional silicon oxide (SiOx) material is dissolved in water, and polymethyl methacrylate (PMMA) and conductive polymer materials are doped by hydrothermal synthesis. Due to its unique "core-shell" structure and high adhesion, polymethyl methacrylate (PMMA) enables the modified silicon oxide material to have lower resistance and excellent stability.

[0023] 2. The introduction of conductive polymer materials in the scheme can not only improve the conductivity of conventional silicon-oxygen materials and improve the initial charge and discharge efficiency of the battery end; but also the excellent adhesion can further improve the cycle stability of silicon-oxygen materials.

[0024] 3. In the scheme, by introducing a silicon-containing binder into the binder, the dispersibility, adhesion, thermal stability and ion mobility of the positive electrode slurry are further improved, the flexibility and elasticity of the cross-linked structure are improved, the internal resistance is reduced, cracks and fractures are reduced, and the electrical performance and electrical cycle stability are improved. DETAILED DESCRIPTION

[0025] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0026] It should be noted that the following parts are by mass, and all raw material purchase manufacturers involved in the present invention are not subject to any special restrictions and are exemplified as follows: In the following embodiments, the model of SiOx material is BSO-L, purchased from B&T Company; the model of PMMA is FS420, purchased from Indile; and bisaminosilane oligomer is purchased from Huangshan Jiahua Silicone Technology Co., Ltd.

[0027] The solid content of the polymethyl methacrylate PMMA emulsion is 15%.

[0028] Embodiment 1: A preparation method for improving the charge-discharge efficiency and cycle performance of silicon-oxygen negative electrode materials, comprising the following steps: Step 1: Add SiOx material into deionized water, add polymethyl methacrylate PMMA emulsion and conductive polymer material polyaniline PANI, stir and mix well, and place in a reaction kettle. The mass ratio of SiOx material to polymethyl methacrylate PMMA solid is 125:1, and the mass ratio of SiOx material to conductive polymer material polyaniline PANI is 105:1. Bake at 180°C for 12h, cool, and obtain modified SiOx material; Step 2: Evenly mix the modified SiOx material, conductive agent Super P (Swiss Temeco), and binder LA133 (Indile), with the mass ratio of modified SiOx material, binder, and conductive agent being 8:1:1, to obtain a negative electrode slurry; coat the negative electrode slurry on a 10um copper foil, and dry it at 100°C for 12h to obtain a silicon-oxygen negative electrode material.

[0029] Embodiment 2: A preparation method for improving the charge-discharge efficiency and cycle performance of silicon-oxygen negative electrode materials, comprising the following steps: Step 1: Add SiOx material into deionized water, add polymethyl methacrylate PMMA emulsion and conductive polymer material polyaniline PANI, stir and mix well, and place in a reaction kettle. The mass ratio of SiOx material to polymethyl methacrylate PMMA solid is 115:1, and the mass ratio of SiOx material to conductive polymer material polyaniline PANI is 105:1. Bake at 180°C for 12h, cool, and obtain modified SiOx material; Step 2: Evenly mix the modified SiOx material, Super P (Swiss Temeco), and binder LA133 (Indile), with the mass ratio of modified SiOx material, binder, and conductive agent being 8:1:1, to obtain a negative electrode slurry; coat the negative electrode slurry on a 10um copper foil, and dry at 100°C for 12h to obtain a silicon-oxygen negative electrode material.

[0030] Embodiment 3: A preparation method for improving the charge-discharge efficiency and cycle performance of silicon-oxygen negative electrode materials, comprising the following steps: Step 1: Add SiOx material into deionized water, add polymethyl methacrylate PMMA emulsion and conductive polymer material polyaniline PANI, stir and mix well, and place in a reaction kettle. The mass ratio of SiOx material to polymethyl methacrylate PMMA solid is 120:1, and the mass ratio of SiOx material to conductive polymer material polyaniline PANI is 105:1. Bake at 180°C for 12h, cool, and obtain modified SiOx material; Step 2: Evenly mix the modified SiOx material, Super P (Swiss Temeco), and binder LA133 (Indile), with the mass ratio of modified SiOx material, binder, and conductive agent being 8:1:1, to obtain a negative electrode slurry; coat the negative electrode slurry on a 10um copper foil, and dry at 100°C for 12h to obtain a silicon-oxygen negative electrode material.

[0031] Embodiment 4: A preparation method for improving the charge-discharge efficiency and cycle performance of silicon-oxygen negative electrode materials, comprising the following steps: Step 1: Add SiOx material into deionized water, add polymethyl methacrylate PMMA emulsion and conductive polymer material polyaniline PANI, stir and mix well, and place in a reaction kettle. The mass ratio of SiOx material to polymethyl methacrylate PMMA solid is 130:1, and the mass ratio of SiOx material to conductive polymer material polyaniline PANI is 105:1. Bake at 180°C for 12h, cool, and obtain modified SiOx material; Step 2: Evenly mix the modified SiOx material, Super P (Swiss Temeco), and binder LA133 (Indile), with the mass ratio of modified SiOx material, binder, and conductive agent being 8:1:1, to obtain a negative electrode slurry; coat the negative electrode slurry on a 10um copper foil, and dry at 100°C for 12h to obtain a silicon-oxygen negative electrode material.

[0032] Embodiment 5: A preparation method for improving the charge-discharge efficiency and cycle performance of silicon-oxygen negative electrode materials, comprising the following steps: Step 1: Add SiOx material into deionized water, add polymethyl methacrylate PMMA emulsion and conductive polymer material polyaniline PANI, stir and mix well, and place in a reaction kettle. The mass ratio of SiOx material to polymethyl methacrylate PMMA solid is 135:1, and the mass ratio of SiOx material to conductive polymer material polyaniline PANI is 105:1. Bake at 180°C for 12h, cool, and obtain modified SiOx material; Step 2: Evenly mix the modified SiOx material, Super P (Swiss Temeco), and binder LA133 (Indile), with the mass ratio of modified SiOx material, binder, and conductive agent being 8:1:1, to obtain a negative electrode slurry; coat the negative electrode slurry on a 10um copper foil, and dry at 100°C for 12h to obtain a silicon-oxygen negative electrode material.

[0033] Example 6: A preparation method for improving the charge-discharge efficiency and cycle performance of silicon-oxygen negative electrode materials, comprising the following steps: Step 1: Add SiOx material into deionized water, add polymethyl methacrylate PMMA emulsion and conductive polymer material polyaniline PANI, stir and mix well, and place in a reaction kettle. The mass ratio of SiOx material to polymethyl methacrylate PMMA solid is 125:1, and the mass ratio of SiOx material to conductive polymer material polyaniline PANI is 95:1. Bake at 180°C for 12h, cool, and obtain modified SiOx material; Step 2: Evenly mix the modified SiOx material, Super P (Swiss Temeco), and binder LA133 (Indile), with the mass ratio of modified SiOx material, binder, and conductive agent being 8:1:1, to obtain a negative electrode slurry; coat the negative electrode slurry on a 10um copper foil, and dry at 100°C for 12h to obtain a silicon-oxygen negative electrode material.

[0034] Example 7: A preparation method for improving the charge-discharge efficiency and cycle performance of silicon-oxygen negative electrode materials, comprising the following steps: Step 1: Add SiOx material into deionized water, add polymethyl methacrylate PMMA emulsion and conductive polymer material polyaniline PANI, stir and mix well, and place in a reaction kettle. The mass ratio of SiOx material to polymethyl methacrylate PMMA solid is 125:1, and the mass ratio of SiOx material to conductive polymer material polyaniline PANI is 100:1. Bake at 180°C for 12h, cool, and obtain modified SiOx material; Step 2: Evenly mix the modified SiOx material, Super P (Swiss Temeco), and binder LA133 (Indile), with the mass ratio of modified SiOx material, binder, and conductive agent being 8:1:1, to obtain a negative electrode slurry; coat the negative electrode slurry on a 10um copper foil, and dry at 100°C for 12h to obtain a silicon-oxygen negative electrode material.

[0035] Embodiment 8: A preparation method for improving the charge-discharge efficiency and cycle performance of silicon-oxygen negative electrode materials, comprising the following steps: Step 1: Add SiOx material into deionized water, add polymethyl methacrylate PMMA emulsion and conductive polymer material polyaniline PANI, stir and mix well, and place in a reaction kettle. The mass ratio of SiOx material to polymethyl methacrylate PMMA solid is 125:1, and the mass ratio of SiOx material to conductive polymer material polyaniline PANI is 110:1. Bake at 180°C for 12h, cool, and obtain modified SiOx material; Step 2: Evenly mix the modified SiOx material, Super P (Swiss Temeco), and binder LA133 (Indile), with the mass ratio of modified SiOx material, binder, and conductive agent being 8:1:1, to obtain a negative electrode slurry; coat the negative electrode slurry on a 10um copper foil, and dry at 100°C for 12h to obtain a silicon-oxygen negative electrode material.

[0036] Example 9: A preparation method for improving the charge-discharge efficiency and cycle performance of silicon-oxygen negative electrode materials, comprising the following steps: Step 1: Add SiOx material into deionized water, add polymethyl methacrylate PMMA emulsion and conductive polymer material polyaniline PANI, stir and mix well, and place in a reaction kettle. The mass ratio of SiOx material to polymethyl methacrylate PMMA solid is 125:1, and the mass ratio of SiOx material to conductive polymer material polyaniline PANI is 115:1. Bake at 180°C for 12h, cool, and obtain modified SiOx material; Step 2: Evenly mix the modified SiOx material, Super P (Swiss Temeco), and binder LA133 (Indile), with the mass ratio of modified SiOx material, binder, and conductive agent being 8:1:1, to obtain a negative electrode slurry; coat the negative electrode slurry on a 10um copper foil, and dry at 100°C for 12h to obtain a silicon-oxygen negative electrode material.

[0037] Embodiment 10: A preparation method for improving the charge-discharge efficiency and cycle performance of silicon-oxygen negative electrode materials, comprising the following steps: Step 1: (1) Under nitrogen atmosphere, 5.5 parts of bisaminosilane oligomer, 2.5 parts of triethylenetetramine, 4.5 parts of 2-(methyl methacrylate)ethyl ester-3,5-diaminobenzoic acid, and 4.5 parts of thiocarbonyldiimidazole are added to 90 parts of N-methylpyrrolidone, reacted at 30°C for 20 hours, and capped with 2.5 parts of phenylpropanol. The mixture is diluted with acetone, and then precipitated with ethyl acetate, washed, and centrifuged at 7600 r / min for 12 minutes, repeated 2.5 times, dried, and then dried at 85°C for 13 hours to obtain a silicon-containing intermediate; (2) 15 parts of the silicon-containing intermediate, 2.5 parts of mercaptoaniline, 1.5 parts of mercaptosiloxane, and 0.11 parts of AIBN are added to 90 parts of DMF, exposed to ultraviolet light at room temperature for 2.5 hours, washed, and dried to obtain a silicon-containing adhesive; Step 2: Add SiOx material into deionized water, add polymethyl methacrylate PMMA emulsion and conductive polymer material polyaniline PANI, stir and mix well, and place in a reaction kettle, the mass ratio of SiOx material to polymethyl methacrylate PMMA solid is 125:1, the mass ratio of SiOx material to conductive polymer material polyaniline PANI is 105:1, bake at 180°C for 12h, cool, and obtain modified SiOx material; Step 3: The mass ratio of the modified SiOx material, Super P (Swiss Temeco), binder LA133 (Indile) LA type water-based binder and silicon-containing binder is 7.5:2.5, mixed evenly, and the mass ratio of the modified SiOx material, binder and conductive agent is 8:1:1 to obtain a negative electrode slurry; the negative electrode slurry is coated on a 10um copper foil and dried at 100°C for 12h to obtain a silicon-oxygen negative electrode material.

[0038] Comparative Example 1: Based on Example 1, no polymethyl methacrylate PMMA emulsion is introduced, and the other processes remain unchanged, specifically: Step 1: Add SiOx material into deionized water, add conductive polymer material polyaniline PANI, stir and mix, then place in a reactor, the mass ratio of SiOx material to conductive polymer material polyaniline PANI is 105:1, bake at 180°C for 12h, cool, and obtain modified SiOx material; Step 2: Evenly mix the modified SiOx material, Super P (Swiss Temeco), and binder LA133 (Indile), with the mass ratio of modified SiOx material, binder, and conductive agent being 8:1:1, to obtain a negative electrode slurry; coat the negative electrode slurry on a 10um copper foil, and dry at 100°C for 12h to obtain a silicon-oxygen negative electrode material.

[0039] Comparative Example 2: Based on Example 1, no conductive polymer material PANI is introduced, and the other processes remain unchanged, specifically: Step 1: Add SiOx material into deionized water, add polymethyl methacrylate (PMMA) emulsion, stir and mix, and place in a reaction kettle. The mass ratio of SiOx material to polymethyl methacrylate (PMMA) solid is 125:1. Bake at 180°C for 12h, cool, and obtain modified SiOx material. Step 2: Evenly mix the modified SiOx material, Super P (Swiss Temeco), and binder LA133 (Indile), with the mass ratio of modified SiOx material, binder, and conductive agent being 8:1:1, to obtain a negative electrode slurry; coat the negative electrode slurry on a 10um copper foil, and dry at 100°C for 12h to obtain a silicon-oxygen negative electrode material.

[0040] Comparative Example 3: Based on Example 1, ordinary SiOx material is used as the negative electrode material, and the other processes remain unchanged, specifically: Step 1: Evenly mix SiOx material, conductive agent and binder, the mass ratio of SiOx material, binder and conductive agent is 8:1:1, and obtain negative electrode slurry; coat the negative electrode slurry on 10um copper foil, dry at 100℃ for 12h, and obtain silicon-oxygen negative electrode material.

[0041] Comparative Example 4: Based on Example 10, mercaptoaniline was not added, and the other processes remained unchanged, specifically: Step 1: (1) Under nitrogen atmosphere, 5.5 parts of bisaminosilane oligomer, 2.5 parts of triethylenetetramine, 4.5 parts of 2-(methyl methacrylate)ethyl ester-3,5-diaminobenzoic acid, and 4.5 parts of thiocarbonyldiimidazole are added to 90 parts of N-methylpyrrolidone, reacted at 30°C for 20 hours, and capped with 2.5 parts of phenylpropanol. The mixture is diluted with acetone, and then precipitated with ethyl acetate, washed, and centrifuged at 7600 r / min for 12 minutes, repeated 3 times, dried, and then dried at 85°C for 13 hours to obtain a silicon-containing intermediate; (2) 15 parts of the silicon-containing intermediate, 4 parts of mercaptosiloxane, and 0.11 parts of AIBN are added to 90 parts of DMF, exposed to ultraviolet light at room temperature for 2.5 hours, washed, and dried to obtain a silicon-containing adhesive; Step 2: Add SiOx material into deionized water, add polymethyl methacrylate PMMA emulsion and conductive polymer material polyaniline PANI, stir and mix well, and place in a reaction kettle, the mass ratio of SiOx material to polymethyl methacrylate PMMA solid is 125:1, the mass ratio of SiOx material to conductive polymer material polyaniline PANI is 105:1, bake at 180°C for 12h, cool, and obtain modified SiOx material; Step 3: The mass ratio of the modified SiOx material, Super P (Swiss Temeco), binder LA133 (Indile) LA type water-based binder and silicon-containing binder is 7.5:2.5, mixed evenly, and the mass ratio of the modified SiOx material, binder and conductive agent is 8:1:1 to obtain a negative electrode slurry; the negative electrode slurry is coated on a 10um copper foil and dried at 100°C for 12h to obtain a silicon-oxygen negative electrode material.

[0042] Testing experiment: A silicon-oxygen negative electrode material prepared in Examples 1 to 10 and Comparative Examples 1 to 4 was used to prepare a button battery, a CR2032 button battery shell was selected, and a 20 um separator was selected, and then its related performance was tested; the specific process is as follows: Step 1: In a glove box filled with argon, place the negative electrode on the battery shell, drip the electrolyte, place the diaphragm, drip the electrolyte, place the lithium sheet, place the gasket shrapnel, and finally cap the battery shell to obtain a button battery; Step 2: The obtained button battery is subjected to a cycle performance test and an initial charge and discharge efficiency test; specifically: (1) Cycle performance test: The button batteries prepared in Examples 1 to 10 and Comparative Examples 1 to 4 are subjected to a 0.2C charge and discharge test for 50 cycles using a button battery charge and discharge tester (Wuhan Blue Electric, CT2001A), with a voltage range of 0.01 to 3.0 V; (2) Initial charge and discharge efficiency test: The button batteries prepared in Examples 1 to 10 and Comparative Examples 1 to 4 are subjected to a 0.2C charge and discharge test using a button battery charge and discharge tester (Wuhan Blue Electric, CT2001A), with a voltage range of 0.01 to 3.0 V.

[0043] The test results are shown in the table:

[0044] Result analysis: According to the data analysis in Table 1, it can be seen that the conventional one-step hydrothermal method is used in the present application to prepare the modified SiOx material. The conventional silicon oxide (SiOx) material is dissolved in water, and PMMA and the conductive polymer material are doped by the hydrothermal synthesis method. PMMA has a unique "core-shell" structure and high adhesion, so that the modified silicon oxide material can have lower resistance and excellent stability; in addition, the introduction of the conductive polymer material can not only improve the conductivity of the conventional silicon oxide material and improve the initial charge and discharge efficiency of the battery end; and the excellent adhesion can further improve the cycle stability of the silicon oxide material.

[0045] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A preparation method for improving the charge-discharge efficiency and cycle performance of silicon-oxygen negative electrode materials, characterized in that: The following steps are involved: Step 1: Add SiOx material to pure water, add polymethyl methacrylate emulsion and conductive polymer material and stir evenly, transfer to a reactor for thermal reaction, filter and dry to obtain modified SiOx material; Step 2: Use the modified SiOx material to prepare silicon-oxygen negative electrode material.

2. A method for preparing a silicon-oxygen negative electrode material for improving charge-discharge efficiency and cycle performance according to claim 1, characterized in that: The solid content of the polymethyl methacrylate emulsion is 14.5-15.5%; the mass ratio of the SiOx material to the solid in the polymethyl methacrylate emulsion is 115-135:

1.

3. The method for preparing a silicon-oxygen negative electrode material for improving charge-discharge efficiency and cycle performance according to claim 1, characterized in that: The mass ratio of the SiOx material to the conductive polymer material is 95-115:

1.

4. The method for preparing a silicon-oxygen negative electrode material for improving charge-discharge efficiency and cycle performance according to claim 1, characterized in that: In step 1, the reaction conditions are: baking at 180-200° C. for 12-16 hours; The specific steps of step 2 are: uniformly mixing the modified SiOx material, the binder, and the conductive agent to obtain a negative electrode slurry; coating the negative electrode slurry on the current collector, and drying at 100-120° C. for 12-16 hours to obtain a silicon-oxygen negative electrode material.

5. A method for preparing a silicon-oxygen negative electrode material for improving charge-discharge efficiency and cycle performance according to claim 4, characterized in that: The raw materials of the negative electrode slurry include a modified SiOx material, a binder, and a conductive agent in a mass ratio of 8:1:

1.

6. A preparation method for improving the charge-discharge efficiency and cycle performance of silicon-oxygen negative electrode materials according to claim 4, characterized in that: The current collector includes copper foil; the thickness of the current collector is 6-10 μm.

7. The method for preparing a silicon-oxygen negative electrode material for improving charge-discharge efficiency and cycle performance according to claim 1, characterized in that: The adhesive includes one or both of an LA type water-based adhesive and a silicon-containing adhesive.

8. A method for preparing a silicon-oxygen negative electrode material for improving charge-discharge efficiency and cycle performance according to claim 7, characterized in that: The adhesive is composed of an LA type water-based adhesive and a silicon-containing adhesive, wherein the silicon-containing adhesive accounts for 20-30wt% of the total amount of the adhesive.

9. The method for preparing a silicon-oxygen negative electrode material for improving charge-discharge efficiency and cycle performance according to claim 7, characterized in that: The preparation method of the silicon-containing binder is: Step 1: (1) under nitrogen atmosphere, add bisaminosilane oligomer, triethylenetetramine, 2-(methylacrylate)ethyl-3,5-diaminobenzoic acid, and thiocarbonyldiimidazole to N-methylpyrrolidone, react at 25-35° C. for 18-24 hours, add phenylpropanol for end-capping, and post-treat to obtain a silicon-containing intermediate; Step 2: Add the silicon-containing intermediate, mercaptoaniline, mercaptosiloxane and azobisisobutyronitrile to N,N-dimethylformamide, irradiate with ultraviolet light for 2 to 3 hours at room temperature, wash and dry to obtain a silicon-containing adhesive.

10. A preparation method for improving the charge-discharge efficiency and cycle performance of silicon-oxygen negative electrode materials according to claim 9, characterized in that: The raw materials of the silicon-containing intermediate include the following components: by mass, 5-6 parts of bisaminosilane oligomer, 2-3 parts of triethylenetetramine, 4-5 parts of thiocarbonyldiimidazole, 4-5 parts of 2-(methacrylate)ethyl-3,5-diaminobenzoic acid, 2-3 parts of phenylpropanol, and 80-100 parts of N-methylpyrrolidone; The raw materials of the silicon-containing adhesive include the following components: 14 to 16 parts of silicon-containing intermediate, 2 to 3 parts of mercaptoaniline, 1 to 2 parts of mercaptosiloxane, 0.1 to 0.12 parts of azobisisobutyronitrile, and 80 to 100 parts of N,N-dimethylformamide, in parts by mass.